A new species of Dravidogecko (Squamata: Gekkonidae) from the under-surveyed Periyar Plateau of the Southern Western Ghats in Peninsular India - Adhikari, Omkar Dilip; Srikanthan, Achyuthan N.; Ganesh, S.R. (European Journal of Taxonomy, 2023)
We describe a new species of Dravidogecko from the poorly-inventoried Periyar Plateau of Southern Western Ghats, Peninsular India. The new species Dravidogecko beddomei sp. nov. is characterized by: precloacal-femoral pores 46‒52; scales across belly 31‒33; supralabials 9–11; infralabials 8–9; lamellae on digit IV of pes 10–11. Additionally, the new species is divergent (>13%) from its related congeners. Like its congeners, the new species is currently known only from its type locality and its vicinity – the Devar Malai, Kakki Reservoir – and Sivagiri Hills in the Periyar Plateau of Southern Western Ghats. This discovery further increases the list of new reptiles described from this under-studied massif in the Southern Western Ghats.